Modification in the way of calculating the total energy produced by the solar cells of the remote sensors of the University of Alberta - Moya-Mora, Ana Lucía (2014)
The present article proposes an improvement in the calculus ofthe amount of energy produced by the solar cells of remote sensors built in the University of Alberta, Edmonton, Canada. Therebyit was determined that for those sites where the University have installed the devices, the cells must be placed on an angle of 25 °. Besides it was posed the calculus of the amount of radiation absorbed by the sensor cover, thus it was modifiedthe corresponding value of maximum radiation amount that reaches the cells and it is proposed to add these formulas to the algorithm used to calculate the total energy produced by the solar cells. Finally, it were pointed out the changes brought in the calculation of the total amount of energy as a result of above changes.